ANALISIS KREATIVITAS PESERTA DIDIK DALAM MEMECAHKAN MASALAH MATEMATIKA BERBASIS HOTS - Ahmad, Nuril Khasbillah Amin; Zamzam, Kenys Fadhilah (Universitas Insan Budi Utomo, 2025)
This study began with the importance of developing students' creativity in solving mathematical story problems. The learning process generally focuses on textbooks and solving problems using the formulas available in them, tending to limit students' creative thinking skills. This results in students being less trained in finding various alternative solutions in dealing with contextual problems, especially in the material of sequences and series. The purpose of this study was to complete the measure of creativity of Islamic-Islamic high schools in mathematical narrative resolution based on higher order thinking about thinking. The subjects of this study consisted of five students of Class VIII, whose middle skills were classified. The results showed that there was a relationship between students' creative mathematical skills in solving problems. The analysis of five students working on higher-order thinking skills problems revealed significant variation in their analytical comprehension and creativity. The first and second students demonstrated low levels of analytical comprehension. The third student had a fairly good analytical comprehension, but still showed limitations in creativity. The fourth student demonstrated better development in terms of conceptual understanding, analytical skills, and problem-solving creativity. The fifth student demonstrated the most outstanding ability, not only possessing a high level of conceptual understanding and analytical skills, but also being able to solve problems using creative, efficient, and easily understood strategies.